2010
DOI: 10.1007/s10811-010-9561-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of a cytosolic Hsp70 gene from Ulva pertusa (Ulvophyceae, Chlorophyta)

Abstract: In this study, homologous cloning coupled with the rapid amplification of cDNA ends was used to clone a full-length cytosolic heat shock protein 70 of Ulva pertusa (designated as UPHsp70). Bioinformatics was used to analyze structural features, homologous relationship, and phylogenetic position of UPHsp70. The full length of UPHsp70 cDNA was 2,283 bp, with a 5′ untranslated region of 65 bp, a 3′ untranslated region of 247 bp, and an open reading frame of 1,971 bp encoding a polypeptide of 656 amino acids with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Different from U. pertusa (Fu et al, 2011), the hsp70 transcription in U. prolifera was less affected by desiccation; it indirectly reflected that U. prolifera exhibited less adaption to desiccation. This was consistent with previous studies in which photosynthetic of U. pertusa showed little difference after the desiccation treatment (Zou and Gao, 2003;Guo and Dong, 2008).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Different from U. pertusa (Fu et al, 2011), the hsp70 transcription in U. prolifera was less affected by desiccation; it indirectly reflected that U. prolifera exhibited less adaption to desiccation. This was consistent with previous studies in which photosynthetic of U. pertusa showed little difference after the desiccation treatment (Zou and Gao, 2003;Guo and Dong, 2008).…”
Section: Discussionmentioning
confidence: 83%
“…Yokthongwattana et al (2001) studied hsp70 activities in the photosystem II damage and repairing in Dunaliella salina. In addition, Fu et al (2011) found that there was a correlation between transcriptions and stress induction in Ulva pertusa and held that hsp70 played an important role in the stresses.…”
Section: Introductionmentioning
confidence: 99%
“…This may potentially be related to gene regulation induced by cold shock as it was found that overexpression of ERG10 enhanced survival and growth of yeast when frozen at -200 o C for five days (Rodriguez-Vargas et al, 2002). Whereas the expression of heat shock proteins (HSP) was not determined in the current study, HSP gene clones are available for U. pertusa (Tominaga et al, 2010) and U. prolifera (Fu et al, 2011). The subsequent decrease in regrowth rate with time may relate to bacterial activity and the subsequent mortality of the Ulva germlings.…”
Section: Discussionmentioning
confidence: 85%
“…The expression level of Ap‐sHSP 19.1 gene was low in cold conditions and significantly elevated in response to temperature increase. However, Ap‐sHSP 19.1 expression was significantly decreased after exposure to high temperature stress (50°C; Figure ), this may be considered as the activity of enzymes related to the HSP mRNA synthesis was inhibited by high temperature (Fu et al, ; Wei et al, ). Our data suggest that the Ap‐sHSP19.1 gene plays a crucial role in thermal tolerance.…”
Section: Discussionmentioning
confidence: 99%